Book Review: Waqf, Effective Arrangement and Governance - Maliha, Hasna (SMART Insight, 2025)
Waqf is one of the Islamic social financial instruments that has great potential in supporting social and economic development, especially in countries with a majority Muslim population. In the context of modern development challenges—such as structural poverty, income inequality, and limited public financing—waqf offers an alternative to sustainable financing based on Islamic philanthropic values. This article develops and synthesizes the main idea of the book Waqf: Effective Regulation and Governance (Bank Indonesia & Department of Sharia Economics FEB, Universitas Airlangga, 2016) into a comprehensive review. The discussion included the socio-economic conditions of Muslim countries, the theory and practice of waqf, legal and regulatory frameworks, nazhir governance, waqf support systems, and comparisons of waqf practices in various countries. This article emphasizes that the success of productive waqf is highly determined by the quality of governance, professionalism of nazhir, the strength of regulations, and the integration of waqf in national development policies. With this approach, waqf has the potential to become a strategic instrument in achieving inclusive and sustainable economic development.